Advancing Our Understanding of the Link between Statistical Learning and Language Acquisition: The Need for Longitudinal Data - Arciuli, Joanne; Torkildsen, Janne V. (Frontiers in Psychology, 2012)
Mastery of language can be a struggle for some children. Amongst those that succeed in achieving this feat there is variability in proficiency. Cognitive scientists remain intrigued by this variation. A now substantial body of research suggests that language acquisition is underpinned by a child's capacity for statistical learning. Moreover, a growing body of research has demonstrated that variability in statistical learning is associated with variability in language proficiency. Yet, there is a striking lack of longitudinal data. To date, there has been no comprehensive investigation of whether a capacity for statistical learning in young children is, in fact, associated with language proficiency in subsequent years. Here we review key studies that have led to the need for this longitudinal research. Advancing the language acquisition debate via longitudinal research has the potential to transform our understanding of typical development as well as disorders such as autism, specific language impairment and dyslexia.